Beyond megachurch myths : what we can learn from America's largest churches - Thumma, Scott, 1957-; Travis, Dave, 1961-; Leadership Network (Dallas, Tex.) (San Francisco, Calif. : Jossey-Bass, 2007)
Drawing on extensive, broad-based, and well-designed research, as well as stories and anecdotes, Beyond Megachurch Myths dispels popluar myths about megachurches while highlighting the diversity within the megachurch phenomenon. Defining a megachurch as a Protestant church that averages at least 2000 total attendees in their weekend services, Scott Thumma and Dave Travis reveal what these churches are and are not, why they are thriving, what their members say about their experiences, and why they have many valuable lessons to teach smaller churches.
The scale and scope of megachurches in America -- "All megachurches are alike" -- "That church is just too big!" -- "Megachurches are cults of personality" -- "These churches are only concerned about themselves and the needs of their attendees" -- "Megachurches water down the faith" -- "These churches are bad for other churches" -- "These churches are full of people of the same race, class, and political preferences" -- "Megachurches grow because of the show" -- "The megachurch movement is dying : young people hate these churches" -- What might the future hold?
"A Leadership Network publication."
Includes bibliographical references (pages 211-216) and index.
Keywords: Big churches; Megachurches